Dominasi Materi Bidang Pengembangan yang Diberikan Guru BK terhadap Siswa SMP Negeri 2 Pariaman - Pratiwi, Utari; Syukur, Yarmis; Sukma, Dina (Siber Nusantara Publisher, 2024)
The service materials provided by guidance and counseling teachers are things that need to be considered and selected according to student needs. The accuracy of providing materials will help meet students' needs. So the selection of service materials for each development area will be different. This research aims to analyze the dominant service sector material provided by guidance and counseling teachers in schools. This type of research uses a descriptive quantitative approach. The research population was all guidance and counseling teachers at SMP Negeri 2 Pariaman. The research sample, namely BK teachers at SMP Negeri 2 Pariaman, was selected using the total sampling formula. The research instruments are interview guidelines and questionnaires. Data were analyzed using the percentage formula. The results this research show that the provision of service materials for the learning development and social fields is the dominant field of material provided in schools. So that the results of this research can become a reference for guidance and counseling teachers in schools to broaden their understanding of the field of social development and learning so that they can choose service materials that are not monotonous, and with this understanding they can support the effectiveness of the services provided.